2013
DOI: 10.3329/rujs.v38i0.16552
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence Aggression as Related to Gender and Birth Order

Abstract: In the present study an attempt was made to find out whether aggressive behaviour is related to gender and birth order of the adolescence. A Bengali version of the aggression scale of Edwards Personal Preference Schedule (EPPS) was administered to one hundred students from different colleges in Rajshahi city. In order to investigate the relationship between aggressive behaviour and gender, they were divided into two groups, male and female and comparisons were made between them, on the basis of the scores obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Finally, birth order of siblings was not reported in this study. This is an important area for future research as the associations between birth order and sibling bullying dynamics are not well understood, with mixed findings on perpetration (Cistaro, 2011; Ellis, 2013; Sultana & Latif, 2013) and no known studies focusing on birth order as a determinant of sibling victimization. Further investigation is needed to explore the impacts of birth order on sibling victimization among adolescents with risky gender‐typed traits.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, birth order of siblings was not reported in this study. This is an important area for future research as the associations between birth order and sibling bullying dynamics are not well understood, with mixed findings on perpetration (Cistaro, 2011; Ellis, 2013; Sultana & Latif, 2013) and no known studies focusing on birth order as a determinant of sibling victimization. Further investigation is needed to explore the impacts of birth order on sibling victimization among adolescents with risky gender‐typed traits.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of birth order was originated by Adler and he endorsed that it has a major role in the human life. 7,12 Birth order variances are common because of siblings trying to contest for the attention of their parents by demanding roles inside the family. Previous researches endorse the results of current study.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, a study supported the notion that males are more aggressive than females. 7 Besides, research has also found aggression differences in reference to age. 8 Birth order is another important factors.…”
Section: Introductionmentioning
confidence: 99%
“…To fight against vulnerability, women and men often employ or use different kinds of techniques and alternatives to cope up in extreme conditions. Both affected men and women seek alternative livelihoods to cope up with the hazardous situation (Sultana et al, 2018).…”
Section: Significance Of the Study And Literature Reviewmentioning
confidence: 99%